Editorial - Killingley, Dermot (Religions of South Asia, 2025)
The five articles in this issue range in time from around the second century BCE to the present, and include four religious traditions: Buddhism, Jainism, Hinduism and Christianity. They involve textual criticism, literary study, dramatic theory, art history, ethnographic fieldwork and colonial and church history—showing how all these traditions and disciplines are within the scope of Religions of South Asia.